2017
DOI: 10.1089/vbz.2017.2127
|View full text |Cite
|
Sign up to set email alerts
|

Brave New Worlds: The Expanding Universe of Lyme Disease

Abstract: Projections around the globe suggest an increase in tick-vectored disease incidence and distribution, and the potential for emergence of novel tick-borne pathogens. Lyme disease is the most common reported tick-borne illness in the Unites States and is prevalent throughout much of central Europe. In recent years, the worldwide burden of Lyme disease has increased and extended into regions and countries where the disease was not previously reported. In this review, we discuss the trends for increasing Lyme dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 146 publications
2
97
0
2
Order By: Relevance
“…Given the incidence of this parasite in the human population and the neurologic consequences of latent infection [68,69], it is important to identify if ticks play a role in the distribution of T. gondii. Among the questions to be answered by future research are which species of ticks are most likely to be viable transmitters, including the study of Ixodes scapularis (Blacklegged or Deer tick)another tick with a rapidly expanding habitat within the US [70]. Early studies indicate a short lifespan of T. gondii within the tick.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Given the incidence of this parasite in the human population and the neurologic consequences of latent infection [68,69], it is important to identify if ticks play a role in the distribution of T. gondii. Among the questions to be answered by future research are which species of ticks are most likely to be viable transmitters, including the study of Ixodes scapularis (Blacklegged or Deer tick)another tick with a rapidly expanding habitat within the US [70]. Early studies indicate a short lifespan of T. gondii within the tick.…”
Section: Expert Opinionmentioning
confidence: 99%
“…A pesar de haber sido descrita en Norteamérica, la borreliosis es endémica en muchos países de Europa y Asia (1,10) . También ha sido descrita en África del Norte (1,11) , Oceanía (12), y Sudamérica (13) .…”
Section: La Enfermedad De Lyme: Un Problema Globalunclassified
“…Las especies del género Borrelia asociadas con la enfermedad de Lyme están agrupadas en un complejo de genoespecies llamadas B.b.s.l., que incluye a la Borrelia burgdorferi sensu stricto (B.b.s.s) (14,15) . Existe cierta especificidad entre Borrelia y garrapata (16)(17)(18) , de modo que las diferentes especies de Borrelia utilizan diferentes vectores para su transmisión en distintas áreas geográficas (1,11) . Más aún, diferentes especies de Borrelia están asociadas con diferentes presentaciones clínicas de la enfermedad (19) .…”
Section: Borrelia Y Vectoresunclassified
“…About 300,000 new cases are diagnosed in the United States annually (3,4). Tick-borne infections are on the rise in the USA and Europe due to a host of different factors including climate change (5,6) and disruption of predator density in suburban areas (7). Recent studies on tick prevalence and pathogen load have identified new geographical areas where vector ticks are present (8), as well as novel tick-borne pathogens present in areas where they had not previously been identified (such as B. miyamotoi in Northern California) (9).…”
Section: Introductionmentioning
confidence: 99%